Whole-rock and isotope geochemistry of Ordovician to Silurian units of the Cuyania terrane, Argentina: insights for the evolution of SW Gondwana margin - Abre, P. (2011)
The Cuyania terrane in central Argentina (Fig. 1) is characterized by a Mesoproterozoic (Grenvillianage) basement with depleted Pb isotopic signatures and Mesoproterozoic Nd model ages resembling basement rocks of the same age from Laurentia (Ramos, 2004; Sato et al., 2004 and references therein). Several authors have proposed para-autochthonous (Aceñolaza et al., 2002; Finney et al., 2005) versus allochthonous (e. g. Ramos et al., 1986; Dalziel et al., 1994; Astini et al., 1995; Thomas and Astini, 1996) geotectonic models for the early Palaeozoic evolution of the Cuyania terrane. The tectonic evolution of the Cuyania terrane is a substantial part of the understanding of the evolution of the western border of southwest Gondwana. Several morphostructural units form the Cuyania composite terrane (Fig. 1; Ramos et al., 1996): The Precordillera s.s., the Western Pampeanas Ranges and the San Rafael and Las Matras blocks. However, the boundaries of the terrane are still not well-constrained (Astini and Dávila, 2004; Porcher et al., 2004; Casquet et al., 2006). A combination of several methodologies including geochemistry, Sm-Nd, Pb-Pb and U-Pb detrital zircon dating was applied to several clastic Ordovician (Los Sombreros, Gualcamayo, Los Azules, La Cantera, Yerba Loca, Empozada, Trapiche, Sierra de la Invernada, Portezuelo del Tontal, Las Vacas, Las Plantas and Alcaparrosa Formations) and Ordovician to Silurian (Don Braulio and La Chilca Formations) units of the Cuyania terrane (Fig. 2). The combination of these different approaches can give accurate information in order to constrain the probable sources that provided detritus to the Cuyania terrane and ultimately to constrain the existing models about its origin.